Silver-aluminum conductive paste, preparation method of silver-aluminum electrode of solar cell and solar cell
The silver-aluminum conductive paste is prepared by combining the first glass powder without boron and the second glass powder with a specific BaO/B2O3 molar ratio, which solves the problem of difficult series resistance and open circuit voltage balance in the silver-aluminum paste, and improves the Conversion efficiency and battery performance of solar cells.
Patent Information
- Application Number
- CN202310808764.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-03
- Publication Date
- 2025-01-07
AI Technical Summary
In the prior art, silver aluminum paste is difficult to achieve a good balance between series resistance and open circuit voltage in solar cells, resulting in limited improvement in conversion efficiency.
The silver aluminum conductive paste is formed by combining a first glass powder without boron and a second glass powder with a specific BaO/B2O3 molar ratio, and the silver aluminum electrode is prepared by patterning printing and sintering to achieve open circuit voltage and series resistance. Better balance.
It improves the conversion efficiency of solar cells, improves the parallel resistance and fill factor, significantly improving battery performance.
Smart Images

Figure BDA0004321216930000241 
Figure BDA0004321216930000251 
Figure BDA0004321216930000261
Abstract
Description
Technical Field
[0001] The present invention generally relates to the field of solar cells, and in particular to a silver-aluminum conductive paste for solar cells, a method for preparing a silver-aluminum electrode for solar cells using the same, and a solar cell. Background Art
[0002] With the consumption of traditional fossil energy and the deterioration of the ecological environment for human survival, clean renewable energy such as solar energy, wind energy, and hydropower have long been highly valued by the world. Among them, solar energy, with its inexhaustible characteristics and advantages, can be said to be the best choice for mankind to solve the energy shortage problem in the 21st century. The core components of photovoltaic power generation are solar cells and modules. The goal is to continuously improve the power conversion efficiency of battery modules and reduce the cost of power generation, so as to ultimately achieve "grid parity".
[0003] At present, P-type crystalline silicon cells occupy the main share of the crystalline silicon cell market. However, from the current perspective, it is increasingly difficult to improve the photoelectric conversion efficiency of P-type cells. It can be said that it has reached a certain bottleneck. At the same time, major changes in the entire market environment and other reasons have gradually led to the continuous development and utilization of N-type crystalline silicon cell technology. Compared with the P-type, the N-type monocrystalline system has the dual advantages of high power generation and high reliability, and is currently becoming the focus of attention of many large manufacturers. The N-type monocrystalline high-efficiency cells currently on the market mainly include: PERL and PERT, HIT, IBC, TOPCon and other solar cells. Among them, TOPCon and HIT have become the most powerful competitors for the next generation of photovoltaic technology after P-type PERC, and TOPCon has quickly become a new technology that can be mass-produced with priority due to its high compatibility with existing production lines, lower cost than HIT, and large room for improvement in conversion efficiency.
[0004] The conductive paste used on the front of the TOPCon battery has gradually transitioned from silver paste to silver-aluminum paste. The reason is that people have gradually discovered that the use of silver-aluminum paste has greater advantages: First, silver-aluminum paste can adapt to lower sintering temperatures, so that it can be co-fired with the back paste to obtain better double-sided conversion efficiency. Second, through the introduction of aluminum powder, effective aluminum doping can be formed at the Ag-Si alloy interface, thereby reducing contact resistance and improving conversion efficiency. Third, it can achieve partial replacement of precious metal silver powder to achieve the effect of reducing costs.
[0005] However, in practical applications, silver-aluminum paste also faces problems that need to be solved urgently, namely, the introduction of aluminum powder will cause the series resistance to increase.
[0006] In summary, the addition of aluminum powder has both advantages and disadvantages, and only by fully balancing the series resistance and open circuit voltage can the conversion efficiency be improved. However, the current existing technology cannot fully avoid the disadvantages of silver aluminum paste.
[0007] Therefore, there is still a need to find a method that can achieve a better balance between the series resistance and the open circuit voltage of a solar cell and can also improve the conversion efficiency at the same time. Summary of the invention
[0008] The present invention is made in view of the above problems existing in the prior art.
[0009] In a first aspect, the present invention provides a silver-aluminum conductive paste, which comprises silver powder, aluminum powder, a first glass powder, a second glass powder and an organic phase, preferably composed of silver powder, aluminum powder, a first glass powder, a second glass powder and an organic phase, wherein:
[0010] The first glass powder comprises the following, preferably consists of the following:
[0011] 30-70 mol%, preferably 40-60 mol%, preferably 43-54 mol% of PbO, 0.5-10 mol%, preferably 1-5 mol%, preferably 1.3-3.5 mol% of Al2O3, 5-50 mol%, preferably 10-40 mol%, preferably 20-31 mol% of SiO2, 2-40 mol%, preferably 5-30 mol%, preferably 8-25 mol% of ZnO, 0-10 mol%, preferably 0-5 mol%, preferably 0-2.5 mol% of Ga2O3, 0-25 mol%, preferably 0-20 mol%, preferably 0-15 mol% of Li2O, and 0-10 mol%, preferably 0-5 mol%, preferably 0-2.5 mol% of Na2O, and the first glass powder does not contain boron;
[0012] The second glass powder includes the following, preferably consists of the following:
[0013] 0-60 mol%, preferably 0-50 mol%, preferably 0-45 mol% PbO, 0-10 mol%, preferably 0-5 mol%, preferably 0-3.0 mol% Al2O3, 5-50 mol%, preferably 10-40 mol%, preferably 20-25 mol% SiO2, 0-30 mol%, preferably 0-20 mol%, preferably 0-15 mol% ZnO, 0.5-20 mol%, preferably 0.8-10 mol%, preferably 1-6 mol% Li2O, 2-70 mol%, preferably 5-65 mol%, preferably 9-56 mol% B2O3, 0-10 mol%, preferably 0-5 mol%, preferably 0-2 mol% Na2O, and 2-60 mol%, preferably 5-50 mol%, preferably 5.5-40 mol% BaO, wherein the BaO / B2O3 molar ratio = 0.15-0.68.
[0014] In a second aspect, the present invention provides a method for preparing a silver-aluminum electrode for a solar cell, comprising the following steps:
[0015] Providing a silver-aluminum conductive paste according to the first aspect of the present invention;
[0016] Printing the silver-aluminum conductive paste in a patterned manner onto the surface of a solar cell substrate, and drying the paste to form a silver-aluminum electrode precursor;
[0017] The silver-aluminum electrode precursor is sintered to form a silver-aluminum electrode on the surface of the solar cell substrate.
[0018] In a third aspect, the present invention further provides a solar cell, comprising a solar cell substrate and a silver-aluminum electrode formed on a surface of the solar cell substrate, wherein the silver-aluminum electrode is prepared by the preparation method according to the second aspect of the present invention.
[0019] A silver-aluminum conductive paste for a solar cell is formed by combining a first glass powder without boron and a second glass powder with a defined BaO / B2O3 molar ratio, and the silver-aluminum conductive paste is used to prepare a silver-aluminum electrode of a solar cell. The solar cell finally prepared can achieve a better balance between open circuit voltage and series resistance (without deteriorating one of the open circuit voltage and series resistance in exchange for the improvement of the other), while improving conversion efficiency. In addition, the prepared solar cell can also have improved parallel resistance and fill factor. DETAILED DESCRIPTION
[0020] In order to make the invention purpose, technical solution and beneficial technical effect of the present application clearer, the present application will be described in detail below. It should be noted that the various aspects, features, implementation methods and advantages described in the present application may be compatible and / or may be combined together.
[0021] Unless otherwise specified, the meanings of the technical terms in this specification are the same as those generally understood by those skilled in the art.
[0022] Relational terms such as “first” and “second” are used merely to distinguish one element, component or method step from another with the same name, but do not necessarily require or imply any such actual relationship or order between these elements, components or method steps.
[0023] The invention relates to a silver-aluminum conductive paste for solar cells, a method for preparing a silver-aluminum electrode for solar cells using the same, and a solar cell.
[0024] The present invention will be described in detail below.
[0025] 1. Silver-aluminum conductive paste
[0026] In a first aspect, the present invention relates to a silver-aluminum conductive paste, which comprises silver powder, aluminum powder, a first glass powder, a second glass powder and an organic phase, wherein:
[0027] The first glass powder includes:
[0028] 30-70 mol% PbO,
[0029] 0.5-10 mol% Al2O3,
[0030] 5-50 mol% SiO2,
[0031] 2-40 mol% ZnO,
[0032] 0-10 mol% Ga2O3,
[0033] 0-25 mol% Li2O, and
[0034] 0-10 mol% Na2O,
[0035] and the first glass powder does not contain boron;
[0036] The second glass powder includes:
[0037] 0-60 mol% PbO,
[0038] 0-10 mol% Al2O3,
[0039] 5-50 mol% SiO2,
[0040] 0-30 mol% ZnO,
[0041] 0.5-20 mol% Li2O,
[0042] 2-70 mol% B2O3,
[0043] 0-10 mol% Na2O, and
[0044] 2-60 mol% BaO,
[0045] Wherein the BaO / B2O3 molar ratio = 0.15-0.68.
[0046] The applicant has found that when the silver-aluminum conductive paste has a defined composition, the solar cell using the paste to prepare the electrode can achieve a better balance of open circuit voltage and series resistance performance (it can improve at least one of the open circuit voltage and the series resistance, while keeping the other at least the same or substantially the same level; or improve both the open circuit voltage and the series resistance at the same time), and improve the conversion efficiency at the same time. In addition, the obtained solar cell can also have improved parallel resistance and fill factor.
[0047] In particular, the applicant has found that when the first glass powder does not contain boron, compared with the case of a corresponding glass powder having the same composition except for containing (e.g., a small amount) of B, a solar cell using the same glass powder to prepare an electrode can obtain a higher open circuit voltage and a higher conversion efficiency, and at the same time, the series resistance is not increased or substantially increased. In addition, it can also achieve a larger short-circuit current, parallel resistance, and fill factor. Therefore, the performance of the resulting solar cell is significantly improved.
[0048] The applicant also found that when the BaO / B2O3 molar ratio of the second glass powder is above 0.15, compared with the second glass powder with a BaO / B2O3 molar ratio lower than 0.15 and the same other composition, the series resistance of the solar cell using it to prepare the electrode is significantly reduced and the conversion efficiency is increased, and the parallel resistance and the fill factor are also increased, while the open circuit voltage is not reduced or basically not reduced, resulting in a significant improvement in battery performance; when the BaO / B2O3 molar ratio of the second glass powder is below 0.68, compared with the second glass powder with a BaO / B2O3 molar ratio higher than 0.68 and the same other composition, the open circuit voltage and conversion efficiency of the solar cell using it to prepare the electrode are increased, and the parallel resistance and the fill factor are also increased, and the series resistance is not increased, resulting in a significant improvement in battery performance.
[0049] In one embodiment, the silver-aluminum conductive paste consists of silver powder, aluminum powder, a first glass powder, a second glass powder and an organic phase.
[0050] First glass powder
[0051] The first glass powder includes:
[0052] 30-70 mol% PbO,
[0053] 0.5-10 mol% Al2O3,
[0054] 5-50 mol% SiO2,
[0055] 2-40 mol% ZnO,
[0056] 0-10 mol% Ga2O3,
[0057] 0-25 mol% Li2O, and
[0058] 0-10 mol% Na2O,
[0059] And the first glass frit does not contain boron.
[0060] In a preferred embodiment, the first glass powder is composed of:
[0061] 30-70 mol% PbO,
[0062] 0.5-10 mol% Al2O3,
[0063] 5-50 mol% SiO2,
[0064] 2-40 mol% ZnO,
[0065] 0-10 mol% Ga2O3,
[0066] 0-25 mol% Li2O, and
[0067] 0-10 mol% Na2O.
[0068] In the present application, unless otherwise specified, when referring to the composition of the first glass powder and the second glass powder, the composition refers to the ratio calculated by converting the amount of each element into the molar amount of the corresponding oxide listed, and then relative to the sum of the molar amounts of all corresponding oxides in the corresponding glass powder. This is also a common expression method in the art.
[0069] The first glass powder may include 30-70 mol%, preferably 40-60 mol%, preferably 43-54 mol% PbO. For example, the first glass powder may include the following amount of PbO: 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70 mol%, or a range defined by any two thereof.
[0070] The first glass powder may include 0.5-10 mol%, preferably 1-5 mol%, preferably 1.3-3.5 mol% Al2O3. For example, the first glass powder may include the following amount of Al2O3: 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0 mol%, or a range defined by any two thereof.
[0071] The first glass powder may include 5-50 mol%, preferably 10-40 mol%, preferably 20-31 mol% SiO2. For example, the first glass powder may include the following amount of SiO2: 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50 mol%, or a range defined by any two thereof.
[0072] The first glass powder may include 2-40 mol%, preferably 5-30 mol%, preferably 8-25 mol% ZnO. For example, the first glass powder may include the following amount of ZnO: 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40 mol%, or a range defined by any two thereof.
[0073] The first glass powder may include 0-10 mol%, preferably 0-5 mol%, preferably 0-2.5 mol% of Ga2O3. For example, the first glass powder may include the following amount of Ga2O3: 0, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0 mol%, or a range defined by any two thereof.
[0074] The first glass powder may include 0-25 mol%, preferably 0-20 mol%, preferably 0-15 mol% of Li2O. For example, the first glass powder may include the following amount of Li2O: 0, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25 mol%, or a range defined by any two thereof.
[0075] The first glass powder may include 0-10 mol%, preferably 0-5 mol%, preferably 0-2.5 mol% Na2O. For example, the first glass powder may include the following amount of Na2O: 0, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0 mol%, or a range defined by any two thereof.
[0076] When the first glass powder does not contain boron and has the above composition, compared with the case of the corresponding glass powder having the same composition except containing (e.g., a small amount) of B, a solar cell using the same glass powder to prepare an electrode can obtain a higher open circuit voltage and a higher conversion efficiency, and at the same time, the series resistance is not increased or substantially increased. In addition, it can also achieve a larger short-circuit current, parallel resistance, and fill factor. Therefore, the performance of the resulting solar cell is significantly improved.
[0077] In one embodiment, the first glass powder does not contain Te and / or Bi and / or W and / or Mo and / or V and / or rare earth metals, and preferably the first glass powder does not contain Te, Bi, W, Mo, V, and rare earth metals. Te, Bi, W, Mo, V, and rare earth metal elements are relatively expensive relative to the elements used in the first glass powder of the present invention. Therefore, the present invention can also obtain a solar cell with improved performance at a reduced price.
[0078] In one embodiment, in the first glass powder, the amount of Al2O3 relative to 1 mol of PbO is 0.01-0.2, preferably 0.03-0.07 mol, for example, it can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20 mol, or the range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0079] In one embodiment, in the first glass powder, the amount of SiO2 relative to 1 mol of PbO is 0.1-2, preferably 0.35-0.70 mol, for example, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0. .85, 0.90, 0.95, 1.00, 1.05, 1.10, 1.15, 1.20, 1.25, 1.30, 1.35, 1.40, 1.45, 1.50, 1.55, 1.60, 1.65, 1.70, 1.75, 1.80, 1.85, 1.90, 1.95, 2.00 mol, or a range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0080] In one embodiment, in the first glass powder, the amount of ZnO relative to 1 mol of PbO is 0.05-1.5, preferably 0.15-0.5 mol, for example, 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, 1.00, 1.05, 1.10, 1.15, 1.20, 1.25, 1.30, 1.35, 1.40, 1.45, 1.50 mol, or a range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0081] In one embodiment, in the first glass powder, the amount of Ga2O3 relative to 1 mol of PbO is 0-5, preferably 0-1.6 mol, for example, 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0 mol, or a range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0082] In one embodiment, in the first glass powder, the amount of Li2O relative to 1 mol of PbO is 0-1, preferably 0-0.35 mol, for example, 0, 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, 1.00 mol, or a range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0083] In one embodiment, in the first glass powder, the amount of Na2O is 0-0.15, preferably 0-0.05 mole, relative to 1 mole of PbO, for example, it can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, or a range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance between open circuit voltage and series resistance, and can also have an improved conversion efficiency, parallel resistance and / or fill factor.
[0084] In one embodiment, in the first glass powder, the amount of SiO2 relative to 1 mol of Al2O3 is 2-50, preferably 6.5-23.5 mol, for example, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11 .0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19.0, 19.5, 20.0, 20.5, 21.0, 21.5, 22.0, 22.5, 23.0, 23.5, 24.0, 24.5 , 25.0, 25.5, 26.0, 26.5, 27.0, 27.5, 28.0, 28.5, 29.0, 29.5, 30.0, 30.5, 31.0, 31.5, 32.0, 32.5, 33.0, 33.5, 34.0, 34.5, 35.0, 35.5, 36.0, 36.5, 37.0, 37.5, 38.0, 38.5, 39.0, 39.5, 40.0, 40.5, 41.0, 41.5, 42.0, 42.5, 43.0, 43.5, 44.0, 44.5, 45.0, 45.5, 46.0, 46.5, 47.0, 47.5, 48.0, 48.5, 49.0, 49.5, 50.0 mol, or a range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0085] In one embodiment, in the first glass powder, the amount of ZnO is 1-10, preferably 5.5-8.0 moles relative to 1 mole of Al2O3, for example, it can be 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0 moles, or a range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0086] In one embodiment, in the first glass powder, the amount of Ga2O3 relative to 1 mol of Al2O3 is 0-5, preferably 0-1.6 mol, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0 mol, or a range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0087] In one embodiment, in the first glass powder, the amount of Li2O relative to 1 mol of Al2O3 is 0-12, preferably 0-10.5 mol, for example, it can be 0, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0 mol, or a range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0088] In one embodiment, in the first glass powder, the amount of Na2O relative to 1 mol of Al2O3 is 0-2, preferably 0-0.75 mol, for example, 0, 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80 , 0.85, 0.90, 0.95, 1.00, 1.05, 1.10, 1.15, 1.20, 1.25, 1.30, 1.35, 1.40, 1.45, 1.50, 1.55, 1.60, 1.65, 1.70, 1.75, 1.80, 1.85, 1.90, 1.95, 2.00 mol, or a range defined by any two of them. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0089] In one embodiment, in the first glass powder, the amount of ZnO relative to 1 mol of SiO2 is 0.1-5, preferably 0.25-1.2 mol, for example, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7 , 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0 mol, or a range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0090] In one embodiment, in the first glass powder, the amount of Ga2O3 relative to 1 mole of SiO2 is 0-0.2, preferably 0-0.08 mole, for example, it can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20 mole, or the range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0091] In one embodiment, in the first glass powder, the amount of Li2O is 0-1.5, preferably 0-0.5 moles relative to 1 mole of SiO2, for example, it can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5 moles, or a range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0092] In one embodiment, in the first glass powder, the amount of Na2O relative to 1 mole of SiO2 is 0-0.3, preferably 0-0.12 mole, for example, it can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30 mole, or the range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0093] The average particle size of the first glass powder is not particularly limited as long as it is suitable for uniform mixing with other components of the silver-aluminum paste and for easily obtaining a silver-aluminum electrode with uniform composition through a solid phase reaction later. In one embodiment, the average particle size (D50, also called median particle size) of the first glass powder is 0.5-5 μm, for example, it can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0 μm, or a range limited by any two of them. Herein, unless otherwise specified, the terms "average particle size" and "median particle size" may be used interchangeably and may be represented by D50 or Dv50, which refers to a particle size at which 50% by volume of the particles have a higher particle size and 50% by volume of the particles have a lower particle size in a cumulative volume distribution curve of the particles.
[0094] Herein, unless otherwise stated, the average particle size or median particle size is measured by a laser scattering method, for example, using a laser particle size analyzer.
[0095] The amount of the first glass powder in the silver-aluminum conductive paste is not particularly limited, but preferably the silver-aluminum conductive paste contains 3.5-7 mass %, preferably 4-6 mass % of the first glass powder. For example, the amount of the first glass powder can be 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0 mass %, or a range defined by any two of them.
[0096] The first glass powder can be prepared as follows: Pb source, Al source, Si source, Zn source, Ga source, Li source and Na source (and optional other sources) as raw materials for the first glass powder are mixed in a defined molar ratio (consistent with the composition of the first glass powder), and then the resulting mixture is sintered, the product is cooled, and optionally crushed and classified.
[0097] The source of each constituent element is not particularly limited and can be various source forms commonly used in the art. In one embodiment, for metal elements such as Pb, Al, Zn, Ga, Li, and Na, the raw materials can be provided in the form of oxides, hydroxides, carbonates, etc. For example, the Pb source can be PbO, Pb(OH)2, and / or PbCO3, the Al source can be Al2O3, Al(OH)3, and / or Al2(CO3)3, the Zn source can be ZnO, Zn(OH)2, and / or ZnCO3, the Ga source can be Ga2O3, Ga(OH)3, and / or Ga2(CO3)3, the Li source can be Li2O, LiOH, and / or Li2CO3, and the Na source can be Na2O, NaOH, and / or Na2CO3. In one embodiment, for non-metallic constituent elements such as Si, the source can be an oxide such as SiO2, or an organic compound such as an organic silicate such as tetraethyl orthosilicate. All or part of one or more sources of metal constituent elements such as Pb, Al, Zn, Ga, Li, and Na can also be provided in the form of silicates (e.g., PbSiO3, Pb2SiO4, Al2(SiO3)3, ZnSiO3, Ga2(SiO3)3, Li2SiO3, Li4SiO4, Na2SiO3, Na4SiO4), etc.
[0098] The sintering can be carried out at a temperature of 1100-1300° C. (e.g., 1100, 1150, 1200, 1250, 1300° C., or a range defined by any two thereof). The sintering can be carried out for 0.5-48 hours or longer, such as 0.5, 1.0, 1.5, 2.0, 2.5, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 15, 20, 24, 36, 48 hours, or a range defined by any two thereof. The sintering can be carried out in an inert atmosphere, or an oxidizing atmosphere such as an air atmosphere. The sintering can be carried out under normal pressure or under pressure.
[0099] The cooling can be performed by a conventional glass quenching process. In one embodiment, the cooling is performed by a water quenching method.
[0100] The pulverization can be performed by conventional methods in the art. In one embodiment, the pulverization can be performed by one or more of ball milling (eg, using a planetary ball mill), roller milling, air flow milling, and the like.
[0101] The classification can be performed by conventional methods in the art. In one embodiment, the classification can be performed by screening using a sieve. The first glass powder obtained by screening can have an average particle size (D50) of 0.5-5 μm, or other values or ranges within the range as described above.
[0102] Second glass powder
[0103] In one embodiment, the second glass powder consists of:
[0104] 0-60 mol% PbO,
[0105] 0-10 mol% Al2O3,
[0106] 5-50 mol% SiO2,
[0107] 0-30 mol% ZnO,
[0108] 0.5-20 mol% Li2O,
[0109] 2-70 mol% B2O3,
[0110] 0-10 mol% Na2O, and
[0111] 2-60 mol% BaO.
[0112] The second glass powder may include 0-60 mol%, preferably 0-50 mol%, preferably 0-45 mol% PbO. For example, the second glass powder may include the following amount of PbO: 0, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60 mol%, or a range defined by any two thereof.
[0113] The second glass powder may include 0-10 mol%, preferably 0-5 mol%, preferably 0-3.0 mol% Al2O3. For example, the second glass powder may include the following amount of Al2O3: 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.8, 1.0, 1.2, 1.5, 2.0, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0 mol%, or a range defined by any two thereof.
[0114] The second glass powder may include 5-50 mol%, preferably 10-40 mol%, preferably 20-25 mol% SiO2. For example, the second glass powder may include the following amount of SiO2: 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50 mol%, or a range defined by any two thereof.
[0115] The second glass powder may include 0-30 mol%, preferably 0-20 mol%, preferably 0-15 mol% ZnO. For example, the second glass powder may include the following amount of ZnO: 0, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 mol%, or a range defined by any two thereof.
[0116] The second glass powder may include 0.5-20 mol%, preferably 0.8-10 mol%, preferably 1-6 mol% of Li2O. For example, the second glass powder may include the following amount of Li2O: 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 mol%, or a range defined by any two thereof.
[0117] The second glass powder may include 2-70 mol %, preferably 5-65 mol %, preferably 9-56 mol % B2O3. 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70 mol %, or a range limited by any two of them.
[0118] The second glass powder may include 0-10 mol%, preferably 0-5 mol%, preferably 0-2 mol% Na2O. For example, the second glass powder may include the following amount of Na2O: 0, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0 mol%, or a range defined by any two thereof.
[0119] The second glass powder may include 2-60 mol %, preferably 5-50 mol %, preferably 5.5-40 mol % of BaO. 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 101, 102, 103, 104, 105, 106, 107, 108, 109, 110
[0120] In the second glass powder, the BaO / B2O3 molar ratio may be 0.15-0.68. For example, the BaO / B2O3 molar ratio in the second glass powder may be 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, or a range defined by any two of them. When the BaO / B2O3 molar ratio of the second glass powder is above 0.15, compared with the second glass powder with a BaO / B2O3 molar ratio lower than 0.15 and the same other compositions, the series resistance of the solar cell using it to prepare the electrode is significantly reduced and the conversion efficiency is increased, and the parallel resistance and the fill factor are also increased, while the open circuit voltage is not reduced or basically not reduced, resulting in a significant improvement in battery performance; when the BaO / B2O3 molar ratio of the second glass powder is below 0.68, compared with the second glass powder with a BaO / B2O3 molar ratio higher than 0.68 and the same other compositions, the open circuit voltage and conversion efficiency of the solar cell using it to prepare the electrode are increased, and the parallel resistance and the fill factor are also increased, and the series resistance is not increased, resulting in a significant improvement in battery performance.
[0121] Preferably, the BaO / B2O3 molar ratio in the second glass powder is 0.32-0.64. When the BaO / B2O3 molar ratio in the second glass powder is within this range, the balance between the series resistance and the open circuit voltage of the obtained solar cell can be further improved, and the conversion efficiency can be further improved, as well as the parallel resistance and / or the fill factor can be improved.
[0122] In one embodiment, the second glass powder does not contain Te and / or Bi and / or W and / or Mo and / or V and / or rare earth metals, and preferably the second glass powder does not contain Te, Bi, W, Mo, V, and rare earth metals. Relative to the elements used in the second glass powder of the present invention, Te, Bi, W, Mo, V, and rare earth metal elements are relatively expensive. Therefore, the present invention can also obtain a solar cell with improved performance at a reduced price.
[0123] In one embodiment, in the second glass powder, the amount of PbO relative to 1 mol of SiO2 is 0-6, preferably 0-2 mol, for example, 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2 .6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0 mol, or a range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0124] In one embodiment, in the second glass powder, the amount of Al2O3 relative to 1 mol of SiO2 is 0-0.4, preferably 0-0.12 mol, for example, 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0. 16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40 mol, or a range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0125] In one embodiment, in the second glass powder, the amount of ZnO relative to 1 mol of SiO2 is 0-2, preferably 0-0.7 mol, for example, 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 mol, or a range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have an improved conversion efficiency, parallel resistance and / or fill factor.
[0126] In one embodiment, in the second glass powder, the amount of Li2O relative to 1 mol of SiO2 is 0.01-0.6, preferably 0.05-0.24 mol, for example, 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25 , 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60 mol, or a range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0127] In one embodiment, in the second glass powder, the amount of B2O3 relative to 1 mol of SiO2 is 0.1-7, preferably 0.4-2.6 mol, and can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0 , 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0 mol, or a range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0128] In one embodiment, in the second glass powder, the amount of Na2O relative to 1 mol of SiO2 is 0-0.3, preferably 0-0.09 mol, for example, it can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.26, 0.27, 0.28, 0.29, 0.30 mol, or a range limited by any two of them. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, while also having improved conversion efficiency, parallel resistance and / or fill factor.
[0129] In one embodiment, in the second glass powder, the amount of BaO relative to 1 mol of SiO2 is 0.1-5, preferably 0.25-1.7 mol, for example, 0.10, 0.15, 0.20, 0.25, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0 mol, or a range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0130] In one embodiment, in the second glass powder, the amount of PbO relative to 1 mol of Li2O is 0-100, preferably 0-37 mol, for example, 0, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 98, 99, 100 mol, or a range defined by any two of them. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0131] In one embodiment, in the second glass powder, the amount of Al2O3 relative to 1 mol of Li2O is 0-6, preferably 0-2.3 mol, for example, 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2. , 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0 mol, or a range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0132] In one embodiment, in the second glass powder, relative to 1 mol of Li2O, ZnO is 0-40, preferably 0-13 mol, for example, it can be 0, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40 mol, or the range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0133] In one embodiment, in the second glass powder, the amount of B2O3 relative to 1 mol of Li2O is 5-50, for example, it can be 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50 mol, or the range defined by any two thereof. Within this range, the glass forming property of the raw material of the second glass powder is good and the open circuit voltage conversion efficiency of the obtained solar cell is increased, and the short circuit current, parallel resistance, and fill factor can also be increased, and the series resistance is reduced, thereby improving the performance. Preferably, the B2O3 / Li2O molar ratio is 6-17; within this range, the glass-forming property of the raw material of the second glass powder is further improved, and the open circuit voltage, short circuit current, parallel resistance, fill factor, conversion efficiency and series resistance of the resulting solar cell are further improved overall, resulting in better performance of the solar cell overall.
[0134] In one embodiment, in the second glass powder, the amount of Na2O relative to 1 mol of Li2O is 0-5, preferably 0-1.7 mol, for example, 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 , 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0 mol, or a range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0135] In one embodiment, in the second glass powder, the amount of BaO relative to 1 mol of Li2O is 1-30, preferably 3-10.5 mol, for example, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 15. , 28.5, 29.0, 29.5, 30.0 mol, or a range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0136] In one embodiment, in the second glass powder, the amount of PbO relative to 1 mol of B2O3 is 0-15, preferably 0-5 mol, for example, it can be 0, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0 mol, or a range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0137] In one embodiment, in the second glass powder, the amount of Al2O3 is 0-1, preferably 0-0.3 mole, relative to 1 mole of B2O3, for example, it can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0 mole, or a range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance between open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0138] In one embodiment, in the second glass powder, the amount of ZnO relative to 1 mol of B2O3 is 0-5, preferably 0-1.6 mol, for example, 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 , 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0 mol, or a range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0139] In one embodiment, in the second glass powder, the amount of Na2O relative to 1 mol of B2O3 is 0-0.6, preferably 0-0.21 mol, for example, 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, 54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60 mol, or a range defined by any two thereof. Within this range, the resulting solar cell can have an improved balance of open circuit voltage and series resistance, and can also have improved conversion efficiency, parallel resistance and / or fill factor.
[0140] The average particle size of the second glass powder is not particularly limited as long as it is suitable for uniform mixing with other components of the silver-aluminum paste and for easily obtaining a silver-aluminum electrode with uniform composition through a solid phase reaction later. In one embodiment, the average particle size (D50, also called median particle size) of the second glass powder is 0.5-5 μm, for example, it can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0 μm, or a range limited by any two of them.
[0141] The amount of the second glass powder in the silver-aluminum conductive paste is not particularly limited, but the silver-aluminum conductive paste preferably contains 0.2-2.0 mass %, preferably 0.3-1.5 mass % of the second glass powder. For example, the amount of the second glass powder can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 mass %, or a range defined by any two of them.
[0142] The second glass powder can be prepared as follows: Pb source, Al source, Si source, Zn source, Li source, B source, Na source and Ba source (and optional other sources) as raw materials for the second glass powder are mixed in a defined molar ratio (consistent with the composition of the second glass powder), and then the resulting mixture is sintered, the product is cooled, and optionally crushed and classified.
[0143] The source of each constituent element is not particularly limited and can be in the form of various sources commonly used in the art. In one embodiment, for metal elements such as Pb, Al, Zn, Li, Na and Ba, the raw materials can be provided in the form of oxides, hydroxides, carbonates, etc. For example, the Pb source can be PbO, Pb(OH)2, and / or PbCO3, the Al source can be Al2O3, Al(OH)3, and / or Al2(CO3)3, the Zn source can be ZnO, Zn(OH)2, and / or ZnCO3, the Li source can be Li2O, LiOH, and / or Li2CO3, the Na source can be Na2O, NaOH, and / or Na2CO3, and the Ba source can be BaO, Ba(OH)2, and / or BaCO3. In one embodiment, for non-metallic constituent elements such as Si and B, the source can be an oxide, or an acid thereof, or an organic (silicon / boric) ester thereof. For example, the Si source can be SiO2, H2SiO3, and / or tetraethyl orthosilicate, and the B source can be B2O3, H2BO3, and / or trimethyl borate. All or part of one or more sources of metal constituent elements such as Pb, Al, Zn, Li, Na and Ba can also be provided in the form of silicate or borate (e.g., PbSiO3, Pb2SiO4, Pb2(BO3)3, Al2(SiO3)3, AlBO3, ZnSiO3, Zn3(BO3)2, Ga2(SiO3)3, GaBO3, Li2SiO3, Li4SiO4, Li3BO3, Na2SiO3, Na4SiO4, Na3BO3) etc.
[0144] The sintering can be carried out at a temperature of 1100-1300° C. (e.g., 1100, 1150, 1200, 1250, 1300° C., or a range defined by any two thereof). The sintering can be carried out, for example, for 30-90 minutes or longer, for example, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90 minutes, or a range defined by any two thereof. The sintering can be carried out in an inert atmosphere, or an oxidizing atmosphere, such as an air atmosphere. The sintering can be carried out under normal pressure or under pressure.
[0145] The cooling can be performed by a conventional glass quenching process. In one embodiment, the cooling is performed by a water quenching method.
[0146] The pulverization can be performed by conventional methods in the art. In one embodiment, the pulverization can be performed by one or more of ball milling (eg, using a planetary ball mill), roller milling, air flow milling, and the like.
[0147] The classification can be performed by conventional methods in the art. In one embodiment, the classification can be performed by screening using a sieve. The second glass powder obtained by screening can have an average particle size (D50) of 0.5-5 μm, or other values or ranges within the range as described above.
[0148] Other ingredients: silver powder, aluminum powder and organic phase
[0149] The silver-aluminum conductive paste also includes silver powder, aluminum powder and an organic phase.
[0150] In one embodiment, the silver aluminum conductive paste contains 75-90 mass %, preferably 78-88 mass % of silver powder. For example, the amount of the silver powder can be 75.0, 75.5, 76.0, 76.5, 77.0, 77.5, 78.0, 78.5, 79.0, 79.5, 80.0, 80.5, 81.0, 81.5, 82.0, 82.5, 83.0, 83.5, 84.0, 84.5, 85.0, 85.5, 86.0, 86.5, 87.0, 87.5, 88.0, 88.5, 89.0, 89.5, 90.0 mass %, or a range defined by any two of them.
[0151] The average particle size of the silver powder is not particularly limited, as long as it is suitable for uniform mixing with other components of the silver aluminum paste and is easy to obtain a silver aluminum electrode with uniform composition through a solid phase reaction. In one embodiment, the average particle size (D50) of the silver powder is 0.5-2.5 μm, for example, it can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5 μm, or a range defined by any two of them.
[0152] In one embodiment, the silver aluminum conductive paste contains 0.5-5 mass %, preferably 1-3 mass % aluminum powder. For example, the amount of the aluminum powder can be 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0 mass %, or a range defined by any two thereof.
[0153] The average particle size of the aluminum powder is not particularly limited, as long as it is suitable for uniform mixing with other components of the silver aluminum paste and subsequent easy to obtain a silver aluminum electrode with uniform composition through a solid phase reaction. In one embodiment, the average particle size (D50) of the aluminum powder is 1-5 μm, for example, it can be 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0 μm, or a range defined by any two thereof.
[0154] In one embodiment, the organic phase may include a polymer and an organic solvent. The polymer and organic solvent may be any polymer and organic solvent that decompose during the slurry sintering process without leaving or substantially leaving any residue.
[0155] In a preferred embodiment, the organic phase may include any one selected from ethyl cellulose, cellulose acetate, polyvinyl butyral (PVB), diethylene glycol butyl ether acetate, ethylene glycol butyl ether acetate, alcohol ester dodeca (i.e., 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate), ethylene glycol dibutyl ether, dimethyl adipate, triacetin, terpineol, tripropylene glycol methyl ether, polyethylene wax, polyester wax, and fatty acid amide wax, or a combination of two or more thereof.
[0156] For example, in one embodiment, the organic phase may include:
[0157] one or more of ethyl cellulose and cellulose acetate;
[0158] Polyvinyl butyral;
[0159] Organic solvents;
[0160] Preferably, the organic solvent comprises: one or more selected from diethylene glycol butyl ether acetate, ethylene glycol butyl ether acetate, alcohol ester dodecanedioate, ethylene glycol dibutyl ether, dimethyl adipate, triacetin, terpineol and tripropylene glycol methyl ether, and
[0161] Optionally, one or more selected from polyethylene wax, polyester wax, and fatty acid amide wax (as a thixotropic agent).
[0162] In one embodiment, the organic phase may include, relative to the total weight of the organic phase:
[0163] (i) 1-15 wt % (e.g., 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 wt %, or a range defined by any two thereof) of one or more selected from ethyl cellulose and cellulose acetate, such as ethyl cellulose;
[0164] (ii) 1-15 wt % (e.g., 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 wt %, or a range defined by any two thereof) of polyvinyl butyral;
[0165] (iii) 65-98 wt % (e.g., 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98 wt % or a range limited by any two thereof) of an organic solvent;
[0166] Preferably, the organic solvent is selected from one or more of diethylene glycol butyl ether acetate, ethylene glycol butyl ether acetate, alcohol ester dodecahydrate, ethylene glycol dibutyl ether, dimethyl adipate, triacetin, terpineol and tripropylene glycol methyl ether;
[0167] For example, the organic solvent may include, relative to the total weight of the organic phase:
[0168] -30-70 wt% (e.g., 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70 wt% or a range defined by any two thereof) of diethylene glycol butyl ether acetate;
[0169] 10-50 wt % (e.g., 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50 wt %, or a range defined by any two thereof) of an alcohol ester dodecahydrate; and
[0170] -5-20 wt% (e.g., 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 wt%, or a range defined by any two thereof) of terpineol; and
[0171] (iv) 0-5 wt% (e.g., 0, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0 wt%, or an amount in a range defined by any two thereof) of one or more selected from polyethylene wax, polyester wax, and fatty acid amide wax (as a thixotropic agent), preferably fatty acid amide wax.
[0172] In one embodiment, the silver aluminum conductive paste contains 2-20% by mass, preferably 6-12% by mass of an organic phase. For example, the amount of the organic phase can be 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20% by mass, or a range defined by any two of them.
[0173] The silver-aluminum conductive paste of the present invention can be prepared by combining the components together and uniformly mixing them.
[0174] 2. Preparation method of silver-aluminum electrode for solar cell
[0175] In a second aspect, the present invention relates to a method for preparing a silver-aluminum electrode for a solar cell, comprising the following steps:
[0176] Providing a silver-aluminum conductive paste according to the first aspect of the present invention;
[0177] Printing the silver-aluminum conductive paste in a patterned manner onto the surface of a solar cell substrate, and drying the paste to form a silver-aluminum electrode precursor;
[0178] The silver-aluminum electrode precursor is sintered to form a silver-aluminum electrode on the surface of the solar cell substrate.
[0179] The patterned printing of the silver-aluminum conductive paste can be performed by any method known in the art, for example, it can be performed by a screen printing method commonly used in the art.
[0180] The drying can be carried out, for example, at a temperature of 200-350° C. (e.g., 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350° C., or a range defined by any two thereof).
[0181] The sintering of the silver aluminum electrode precursor can be performed at a temperature of, for example, 400-850° C., for example, in a temperature-programmed manner at a temperature of, for example, 400-850° C. For example, the sintering temperature can be 400, 450, 500, 550, 600, 700, 750, 800, 850° C., or a range defined by any two thereof. The sintering can be performed for 5s-5 minutes, for example 5-60s, for example 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300s or the range defined by any two thereof. The sintering can be performed in an inert atmosphere, or an oxidizing atmosphere such as an air atmosphere. The sintering can be performed under normal pressure or under pressure.
[0182] 3. Solar Cells
[0183] In a third aspect, the present invention relates to a solar cell, comprising a solar cell substrate and a silver-aluminum electrode formed on the surface of the solar cell substrate, wherein the silver-aluminum electrode is prepared from the silver-aluminum conductive paste according to the first aspect of the present invention or the preparation method according to the second aspect of the present invention.
[0184] The structure of a solar cell is well known in the art and will not be described in detail here.
[0185] By using the silver-aluminum conductive paste of the present invention to prepare electrodes, the solar cell of the present invention can achieve a better balance between open circuit voltage and series resistance (not deteriorating one of the open circuit voltage and series resistance in exchange for the improvement of the other) compared to the solar cell of the prior art, while improving conversion efficiency. In addition, the solar cell of the present invention can also have improved parallel resistance and fill factor.
[0186] Example
[0187] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0188] Example 1: Preparation of the first glass powder
[0189] PbO, Al2O3, SiO2, ZnO, Ga2O3, B2O3, Li2O and Na2O were mixed according to the molar ratio shown in Table 1, and the mixture was fully stirred. The obtained mixture was placed in a platinum crucible, and then the crucible was placed in a muffle furnace at 1200°C, and the glass raw materials were melted for 50 minutes until a uniform glass liquid was formed, and then the glass was quenched by a water quenching method to obtain glass fragments. The glass fragments were then ball-milled for 24h-48h using a planetary ball mill.
[0190] Table 1: Raw materials and composition of the first glass powder (mol%)
[0191]
[0192] D50*: Unless otherwise specified, the D50 in the examples is measured using a laser particle size analyzer (model: LT2200) produced by Zhuhai Zhenli Optical Instrument Co., Ltd.
[0193] Example 2: Preparation of the Second Glass Powder
[0194] PbO, Al2O3, SiO2, ZnO, Li2O, B2O3, Na2O and BaO were mixed according to the molar ratio shown in Table 2, and stirred thoroughly. The obtained mixture was placed in a platinum crucible, and then the crucible was placed in a muffle furnace at 1200°C, and the glass raw materials were melted for 50 minutes until a uniform glass liquid was formed, and then the glass was quenched by a water quenching method to obtain glass fragments. The glass fragments were then ball-milled for 24h-48h using a planetary ball mill.
[0195]
[0196] Example 3: Preparation of silver-aluminum conductive paste
[0197] Silver powder (D50=1.8μm), aluminum powder (D50=2.4μm), a first glass powder and a second glass powder, and an organic phase (including 5 wt% of ethyl cellulose (DOW std-20) and 4 wt% of PVB resin (Kuraray Mowital B16H), and 90 wt% of an organic solvent (including 50 wt% of diethylene glycol butyl ether acetate, 30 wt% of alcohol ester dodecanol, 10 wt% of pine alcohol), and 1 wt% of a thixotropic agent (Disparlon 6500, which is a fatty acid amide wax)) are mixed in the ratios shown in Table 3 below, and then mixed with a planetary mixer, and then mixed and pressed with a three-roll mill, and the fineness is tested with a scraper fineness meter to be less than 8μm, thereby making conductive pastes P1 to P13.
[0198] Table 3: Materials and ratios of silver-aluminum conductive paste
[0199]
[0200] Example 4: Preparation of solar cells
[0201] Each silver-aluminum conductive paste was printed on the front side of an N-type single-crystalline silicon solar cell Si semiconductor substrate (purchased from China JinkoSolar Corporation, 163×163mm, square resistance 100Ω / sq) under the same conditions (i.e., except for the different silver-aluminum conductive pastes used, other conditions for preparing solar cells are exactly the same), and then dried at 250°C for 40s. After that, the back side was printed with a commercial paste (poly-polymer product TN02D7), and then dried at 250°C for 40s in a Maxwell chain sintering furnace, and then sintered at 750°C for a total sintering time of 14s (sintering furnace belt speed: 7.6m / min) to obtain an N-type single-crystalline silicon solar cell, with 12 sheets of each paste printed.
[0202] Example 5: Evaluation of solar cell performance
[0203] The open circuit voltage, short circuit current, series resistance, parallel resistance, fill factor, and conversion efficiency of each prepared solar cell were evaluated using a Sinton IV tester.
[0204] The test results are shown in Table 4 below.
[0205]
[0206] It can be seen from Table 4 that by using the combination of the first glass powder and the second glass powder of the present invention, the obtained solar cell has a better balance between open circuit voltage and series resistance than the comparative solar cell, and has improved conversion efficiency. In particular, it can be seen from Table 4 that:
[0207] - The only difference between P5 and P13 is that the first glass frit (A1) used in P5 does not contain boron, while the first glass frit (A3) used in P13 contains boron. As a result, the solar cell of P5 has a higher open circuit voltage and conversion efficiency than P13, and at the same time has substantially the same series resistance, and additionally has a higher short circuit current, parallel resistance, and fill factor.
[0208] -P5 differs from P11 and P12 in that the molar ratio of BaO / B2O3 in the second glass powder used is different, namely 0.322 (B2), 0.746 (B5) and 0.140 (B6). As a result, compared with P11, the solar cell of P5 has the same series resistance, but higher open circuit voltage and conversion efficiency, and also has higher short circuit current, parallel resistance, and fill factor; compared with P12, the solar cell of P5 has the same open circuit voltage, but lower series resistance and higher conversion efficiency, and also has higher parallel resistance and fill factor.
[0209] The present invention forms a silver-aluminum conductive paste for a solar cell by combining a first glass powder without boron and a second glass powder with a defined BaO / B2O3 molar ratio. The solar cell finally prepared can achieve a better balance between open circuit voltage and series resistance, while improving conversion efficiency. In addition, the prepared solar cell can also have improved parallel resistance and fill factor.
[0210] In addition, it can be seen that the P1-P8 conductive pastes of the present invention have a higher B2O3 / Li2O in the second glass powder than the P9 conductive paste of the present invention, and the resulting solar cells have a significantly higher open circuit voltage, equivalent or lower series resistance, and higher conversion efficiency. In particular, P1 has the same composition as P9 except that the B2O3 / Li2O molar ratio in the second glass powder is higher, and as a result, P1 has a higher open circuit voltage, short circuit current, parallel resistance, fill factor and conversion efficiency, as well as a lower series resistance. This shows that the performance of solar cells can be further improved by controlling the B2O3 / Li2O molar ratio in the second glass powder.
[0211] The above is only an exemplary embodiment of the present invention. It should be noted that, for those skilled in the art, without departing from the inventive concept of the present invention, improvements can be made to the present invention, but these all belong to the protection scope of the present invention.
Claims
1. A silver-aluminum conductive paste, comprising silver powder, aluminum powder, a first glass powder, a second glass powder and an organic phase, preferably consisting of silver powder, aluminum powder, a first glass powder, a second glass powder and an organic phase, wherein: The first glass powder comprises the following, preferably consists of the following: 30-70 mol %, preferably 40-60 mol %, preferably 43-54 mol % of PbO, 0.5-10 mol %, preferably 1-5 mol %, preferably 1.3-3.5 mol % Al2O3, 5-50 mol %, preferably 10-40 mol %, preferably 20-31 mol % SiO2, 2-40 mol %, preferably 5-30 mol %, preferably 8-25 mol % ZnO, 0-10 mol %, preferably 0-5 mol %, preferably 0-2.5 mol % of Ga2O3, 0-25 mol %, preferably 0-20 mol %, preferably 0-15 mol % Li2O, and 0-10 mol %, preferably 0-5 mol %, preferably 0-2.5 mol % of Na2O, and the first glass powder does not contain boron; The second glass powder includes the following, preferably consists of the following: 0-60 mol %, preferably 0-50 mol %, preferably 0-45 mol % of PbO, 0-10 mol %, preferably 0-5 mol %, preferably 0-3.0 mol % of Al2O3, 5-50 mol %, preferably 10-40 mol %, preferably 20-25 mol % SiO2, 0-30 mol %, preferably 0-20 mol %, preferably 0-15 mol % ZnO, 0.5-20 mol %, preferably 0.8-10 mol %, preferably 1-6 mol % Li2O, 2-70 mol %, preferably 5-65 mol %, preferably 9-56 mol % B2O3, 0-10 mol %, preferably 0-5 mol %, preferably 0-2 mol % of Na2O, and 2-60 mol %, preferably 5-50 mol %, preferably 5.5-40 mol % of BaO, Wherein the BaO / B2O3 molar ratio = 0.15-0.
68.
2. The silver-aluminum conductive paste according to claim 1, wherein: The silver-aluminum conductive paste comprises: 75-90 mass %, preferably 78-88 mass % of silver powder, 1-5 mass %, preferably 1-3 mass % of aluminum powder, 3.5-7 mass %, preferably 4-6 mass % of the first glass powder, 0.2-2.0 mass %, preferably 0.3-1.5 mass % of the second glass powder, and 2-20% by mass, preferably 6-12% by mass of organic phase.
3. The silver-aluminum conductive paste according to any one of claims 1 to 2, wherein: In the second glass powder, the BaO / B2O3 molar ratio = 0.32-0.
64.
4. The silver-aluminum conductive paste according to any one of claims 1 to 3, wherein: The first glass powder does not contain Te and / or Bi and / or W and / or Mo and / or V and / or rare earth metals, preferably the first glass powder does not contain Te, Bi, W, Mo, V, and rare earth metals, and / or The second glass frit does not contain Te and / or Bi and / or W and / or Mo and / or V and / or rare earth metals. Preferably, the second glass frit does not contain Te, Bi, W, Mo, V, and rare earth metals.
5. The silver-aluminum conductive paste according to any one of claims 1 to 4, wherein: In the second glass powder, the content of B2O3 is 5 to 50, preferably 6 to 17 mol, relative to 1 mol of Li2O.
6. The silver-aluminum conductive paste according to any one of claims 1 to 5, wherein: The average particle size of the first glass powder is 0.5-5 μm, and / or The average particle size of the second glass powder is 0.5-5 μm.
7. The silver-aluminum conductive paste according to any one of claims 1 to 6, wherein: The average particle size of the silver powder is 0.5-2.5 μm, and / or The average particle size of the aluminum powder is 1-5 μm.
8. The silver-aluminum conductive paste according to any one of claims 1 to 7, wherein: The organic phase includes any one or a combination of two or more of ethyl cellulose, polyvinyl butyral, cellulose acetate, diethylene glycol butyl ether acetate, ethylene glycol butyl ether acetate, alcohol ester dodecahydrate, ethylene glycol dibutyl ether, dimethyl adipate, triacetin, terpineol, tripropylene glycol methyl ether, polyethylene wax, polyester wax, and fatty acid amide wax.
9. A method for preparing a silver-aluminum electrode for a solar cell, comprising the following steps: Providing the silver-aluminum conductive paste according to any one of claims 1 to 8; Printing the silver-aluminum conductive paste in a patterned manner onto the surface of a solar cell substrate, and drying the paste to form a silver-aluminum electrode precursor; The silver-aluminum electrode precursor is sintered to form a silver-aluminum electrode on the surface of the solar cell substrate.
10. A solar cell comprising a solar cell substrate and a silver-aluminum electrode formed on a surface of the solar cell substrate, wherein the silver-aluminum electrode is prepared by the preparation method according to claim 9.